A novel process for demulsification of coconut oil milk emulsions by microwave radiation - Norlia, Che Saad (2010)
The application of microwave radiation demulsification process in separation process has been increasingly important.There is several studies on demulsification using microwave radiation and the results are positive.This research aims to develop a generic but efficient and sustainable water/coconut oil separation method through process intensification and integration based on the application of microwave heating technology.This study is devided into two parts which are demulsification process and emulsion stability.The microwave is set at 720W for 5 minutes. Then the coconut milk is heated using microwave. After that the sample is taken out from microwave to 250ml measurement cylinder which is settling process is occured. The procedure mentioned above is repeated for the power 720W;7 minutes,540W;5 minutes,540W;7 minutes.Each sample was run for 3 times per sample. Lastly the data is recorded.As a conclusion,the volume of water and oil separations for all samples were increased when the settling time was increased by increasing the power of microwave radiation.The microwave has high potential as a method to enhance the demulsification of coconut oil milk.